Dynamics of CD4 Lymphocytes and Viral Load at the Natural History of Perinatal HIV-infection - T. A. Daminov; L. N. Tuychiev; G. K. Khudaykulova (LLC "Diagnostics and Vaccines", 2015)
This article presents the analysis of indicators of CD4 lymphocyte count and viral load in the natural history (in the absence of ART) in perinatally HIV-infected children. It was revealed that perinatal way of transmission is characterized by a higher rate of immunodeficiency progression. It may be associated with intrauterine infection, as well as an early defeat HIV immature immune system of the child. The concentration of virus in perinatally infected children since the beginning of the observation and in 30 months after infection is more than in parenterally infected children in 5 and 2 times, respectively, which determines a infavourable version of the disease in perinatally infected children.